A Portrait of the Engineering-Oriented Natural Science Lesson Plan for Teaching and Learning in 5th Grade Elementary School of Elementary Laboratory UPI Bandung - Anwar, Chaerun; Sopandi, Wahyu; Sa'ud, Udin Syaeudin; Pratiwi, Wiwi Tin (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Lesson plan (RPP) serves as a reference for teachers in implementing the teachinglearning in the classroom. Teachers write lesson plans based on the syllabus that engage students in learning to achieve basic competency curriculum. STEM learning approach has been implemented in primary schools. Engineering as one unit STEM believed to provide insight into the processes and systems that are used to make products of technology, because engineering is an approach to designing interactive objects, learning processes, and systems to meet human needs. This study aims to determine: (1) how the teachers write engineering-oriented lesson plans, (2) the constraints faced in the implementation of the lesson plan teachers in learning science, and (3) the efforts of teachers in overcoming the implementation of the RPP in science learning. This study uses qualitative research and descriptive research. The research subject were 1 teacher and 22 students of class V SD Laboratorium UPI Bandung 2018/2019 school year. Data obtained from interviews, observation and documentation in the form. Data were analysed using data reduction, data presentation and conclusion. The results showed although teachers write engineering-oriented lesson plans and executed in sciece classroom teaching-learning, students have difficulty identifying the problem. Poorly trained students to brainstorm and visualize ideas so difficulty determining the necessary tools and materials. Students have a difficulties to create design, and realize the design. Thus, students become less able to reflect on the results of testing the design to improve the design